Editorial Introduction to Centring Intersex Issues: Global and Local Dimensions - Daniela Crocetti; Fae Garland; David Andrew Griffiths; Surya Monro; Tanya Ní Mhuirthile; Katrina Roen; Prashant Singh; Amets Suess-Schwend (Social Sciences)
This Special Issue showcases the expanding body of international scholarly work within intersex studies [...]